Biomarking Trait Resilience With Salivary Cortisol in Chinese Undergraduates - Lai, Julian C. L.; Leung, Monique O. Y.; Lee, Daryl Y. H.; Lam, Yun Wah; Berning, Karsten (Frontiers in Psychology, 2020)
This study aimed to examine the relationship between trait resilience and salivary cortisol in a group of Chinese undergraduates. The Chinese versions of the Brief Resilience Scale (BRS; Lai and Yue, 2014) and a measure of optimism, the revised Life Orientation Test (Lai, 2009) were administered to 49 Chinese undergraduates who provided self-collected saliva samples six times per day (immediately after waking; 0.5, 3, 6, and 12 h thereafter; and at bedtime) over three consecutive weekdays. The cortisol data were aggregated across the three days to examine the association between resilience and components of the diurnal rhythm of cortisol using multiple regression. The results showed that higher resilience was associated with a stronger cortisol response on awakening and a steeper diurnal decline in cortisol from waking to bedtime. However, resilience had no association with the cortisol output over the course of the day. This pattern of diurnal rhythm is consistent with that typically observed in better-adjusted individuals. Generated by an intensive protocol, these findings clearly indicate the important role of the hypothalamic-pituitary-adrenocortical axis in health and adjustment and contribute to the growing literature on resilience and cortisol in humans.